The lucky wheel - Gilmore, Grace (Gilmore, Grace. Tales from Maple Ridge, 2015)
Each student in Maple Ridge is asked to contribute fifty cents for much needed repairs to the school but Logan has no money, so he decides to sell the buggy wheel he found by the side of the road and carefully fixed, if only he can find a buyer for a single wheel.